2015
DOI: 10.14710/ruang.1.4.251-260
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Pengaruh Perusahaan Perkebunan Kelapa Sawit Terhadap Sektor Unggulan Dan Perekonomian Di Kabupaten Sukamara, Provinsi Kalimantan Tengah

Abstract: <em>Kabupaten Sukamara berdiri pada tahun 2002 yang merupakan pemekaran dari Kabupaten Kotawaringin Barat Provinsi Kalimantan Tengah. Pertumbuhan perekonomian disuatu wilayah dapat dipicu oleh keberadaan suatu investasi, karena investasi merupakan lokomotif pertumbuhan ekonomi disuatu wilayah serta pertumbuhan ekonomi suatu wilayah dapat dilihat dari keberhasilan pembangunan ekonomi di wilayah tersebut. Penelitian ini bertujuan untuk mengidentifikasi pengaruh keberadaan perusahaan perkebunan kelapa sawit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was found that agricultural-related sectoris the primary leading sector among four basic sectors. A more detailed picture shows that it is mainly driven by palm oil plantations [16].…”
Section: Palm Oil Plantation's Contribution To Economic Growthmentioning
confidence: 99%
“…It was found that agricultural-related sectoris the primary leading sector among four basic sectors. A more detailed picture shows that it is mainly driven by palm oil plantations [16].…”
Section: Palm Oil Plantation's Contribution To Economic Growthmentioning
confidence: 99%